Application of the HLSVD Technique to the Filtering of X-Ray Diffraction Data. (3rd April 2007) - Ladisa Ladisa, M. M.; Lamura Lamura, A. A.; Laudadio Laudadio, T. T.; Nico Nico, G. G.
Abstract : A filter based on the Hankel-Lanczos singular value decomposition (HLSVD) technique is presented and applied for the first time to X-ray diffraction (XRD) data. Synthetic and real powder XRD intensity profiles of nanocrystals are used to study the filter performances with different noise levels. Results show the robustness of the HLSVD filter and its capability to extract easily and effciently the useful crystallographic information. These characteristics make the filter an interesting and user-friendly tool for processing of XRD data.